Program uroczystości Święta Morza 1946 roku. - Święto Morza (1946). (Gdynia : [s.n.], 1946)
Afisz z programem.
Keywords: Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- źródła; Sopot (Polska) -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- źródła